1986
DOI: 10.1530/jrf.0.0780733
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Poisson-gamma model to study the influence of gamete concentration on sperm-oocyte fusion in the zona-free hamster egg penetration test

Abstract: A Poisson-gamma distribution model has been developed for studying sperm-oocyte interaction in the zona-free hamster egg penetration test. With the aid of this model we have analysed the relationship between the penetration results achieved with semen of normal fertile men and the concentration of spermatozoa and oocytes used in the assay. From this analysis we have drawn up reference tables estimating the number of spermatozoa and oocytes which must be present in the assay for the result to represent a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…It is interesting that the only hint of benefit from the hamster results was in those men with good motile sperm concentration measurements. Al-though this failed to reach statistical significance, the possible trend is in accordance with previous work which demonstrates that the hamster test will define male fertility in couples with unexplained infertility (Aitken et al, 1984a) and also in donors for an artificial insemination programme (Irving and Aitken, 1987).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is interesting that the only hint of benefit from the hamster results was in those men with good motile sperm concentration measurements. Al-though this failed to reach statistical significance, the possible trend is in accordance with previous work which demonstrates that the hamster test will define male fertility in couples with unexplained infertility (Aitken et al, 1984a) and also in donors for an artificial insemination programme (Irving and Aitken, 1987).…”
Section: Discussionsupporting
confidence: 89%
“…The most likely reason for false negative results in some of the cases was low gamete density. It has been shown that the mathematical probability of egg penetration is substantially reduced if the product of the number of sperm and the number of eggs is less than 50 (Aitken and Elton, 1986). This means that large numbers of hamster eggs have to be used to ensure a valid test of sperm function from a man with severe oligozoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…This was because the method appeared to be convenient and was highly predictive of fertility after artificial insemination (Irvine & Aitken, 1986), or in-vitro fertilization (Aitken et al, 1987), although it was less successful in predicting the outcome of natural intercourse in a group of oligozoospermic men (Hargreave et al, 1988). Furthermore, because this protocol achieves a high hamster egg penetration rate with normal fertile samples, the number of gametes (and hamsters) required to obtain statistically valid data is decreased (Aitken & Elton, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…A pool of control semen was created by mixing a number of ejaculates from fertile donors and cryopreserving it, and a sample from the pool was included in the test every day a hamster oocyte assay was run. The results of preliminary analyses showed no increase in predictive power after penetration rates had been adjusted to a constant concentration of motile spermatozoa (Aitken & Elton, 1986) and the results shown below are uncorrected.…”
Section: Semen Preparation and The Hamster Oocyte Penetration Testmentioning
confidence: 83%